Measuring the Interaction Between Manufacturing and Services - Pilat, Dirk (OECD Science, Technology and Industry Working Papers, 2005)
This paper examines the interaction between services and manufacturing using several types of data and shows that the distinction between manufacturing and services is blurring. Services make important contributions to production, mainly through their direct contribution to total output and final demand, but to some degree also through their indirect contribution via other industries. However, services are more independent from other industries than the manufacturing sector. Most inputs that are necessary to produce services are derived from the services sector itself. Moreover, their role as providers of intermediate inputs to other industries is not yet as strong as that of the manufacturing sector. The paper also shows that a growing share of workers in the manufacturing sector is engaged in services-related occupations. Using a broad definition of service-related workers, up to 50% of manufacturing workers are in such occupations. Using firm-level data the paper finds that, despite anecdotal evidence on a growing share of services turnover within the manufacturing sector, manufacturing enterprises in most countries are not very diversified in their constituting establishment, i.e. they do not have many establishments engaged in services production. Canada is a notable exception in this respect. In other countries, it is likely that diversification primarily occurs at the level of the enterprise group. On the other hand, data on products suggest that manufacturing firms and establishments appear to derive a growing share of turnover from services, notably in countries such as Finland and Sweden